Advances in Data Science and Management Proceedings of ICDSM 2019 - Borah, Samarjeet; Emilia Balas, Valentina; Polkowski, Zdzislaw (Lecture Notes on Data Engineering and Communications Technologies, 2020)
XIV, 563 p. 284 illus., 231 illus. in color.